Vascular patterning sets the stage for macro and micro hepatic architecture. Issue 3 (18th November 2014) - Cast, Ashley E.; Walter, Teagan J.; Huppert, Stacey S.; Trainor, Paul; Johnson, Randy
ABSTRACT Background The liver is a complex organ with a variety of tissue components that require a precise architecture for optimal function of metabolic and detoxification processes. As a result of the delicate orchestration required between the various hepatic tissues, it is not surprising that impairment of hepatic function can be caused by a variety of factors leading to chronic liver disease. Results Despite the growing rate of chronic liver disease, there are currently few effective treatment options besides orthotopic liver transplantation. Better therapeutic options reside in the potential for genetic and cellular therapies that promote progenitor cell activation aiding de novo epithelial and vascular regeneration, cell replacement, or population of bioartificial hepatic devices. In order to explore this area of new therapeutic potential, it is crucial to understand the factors that promote hepatic function through regulating cell identities and tissue architecture. Conclusions In this commentary, we review the signals regulating liver cell fates during development and regeneration and highlight the importance of patterning the hepatic vascular systems to set the groundwork for the macro and micro hepatic architecture of the epithelium. Developmental Dynamics 244:497–506, 2015. © 2014 Wiley Periodicals, Inc.